Function and activity in patients with knee arthroplasty: validity and reliability of a German version of the Lysholm Score and the Tegner Activity Scale (Swiss Medical Weekly, 2014)
OBJECTIVE: The Lysholm score and the Tegner activity scale are widely used for assessing knee function and activity level after knee ligament injuries. This study aimed to asses validity and reliability of the German versions of the Lysholm score (Lysholm-G) and the Tegner activity scale (Tegner-G) in patients after total knee arthroplasty (TKA). METHODS: Two patient groups (